BLOOD PRESSURE EXAMINATION AND EDUCATION ON HYPERTENSION PREVENTION IN RANGING HAMLET, NORTH SATARMESE DISTRICT - Natul, Fransiska Kurniati; Mahu, Safry; Beo, Yosef Andrian; Jakri, Yohanes (LPPM Univ. Ibn Khaldun Bogor, 2026)
Hypertension is a significant global health problem with an increasing prevalence. It is the leading cause of cardiovascular disease and premature death worldwide due to its impact on vital organs and its association with chronic kidney disease, diabetes mellitus, and obesity. Despite the availability of various current management strategies, many patients still fail to achieve adequate blood pressure (BP) control. Cardiovascular mortality related to hypertension continues to rise along with the global increase in chronic kidney disease, diabetes mellitus, and obesity. Therefore, improving BP control must be prioritized urgently. Most individuals are unaware that they suffer from hypertension even when they experience its symptoms. The lack of public awareness in monitoring blood pressure and the limited knowledge about hypertension and its management often result in recurrent increases in blood pressure and, in many cases, severe complications. In Ranging Hamlet, most elderly residents suffer from hypertension, and some even experience multiple complications. Blood pressure screening and hypertension education can help in monitoring and controlling blood pressure, providing understanding on how to prevent or manage hypertension, and raising awareness about adopting a healthy lifestyle to avoid hypertension. This activity began with the preparation and implementation stages. After the community service (PKM) for the elderly conducted on October 18, 2024, the results showed that the elderly participants became aware of their blood pressure levels and gained improved knowledge and understanding of hypertension and its management.